2018
DOI: 10.1016/j.virol.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Using barcoded Zika virus to assess virus population structure in vitro and in Aedes aegypti mosquitoes

Abstract: Arboviruses such as Zika virus (ZIKV, Flaviviridae; Flavivirus) must replicate in both mammalian and insect hosts possessing strong immune defenses. Accordingly, transmission between and replication within hosts involves genetic bottlenecks, during which viral population size and genetic diversity may be significantly reduced. To help quantify these bottlenecks and their effects, we constructed 4 "barcoded" ZIKV populations that theoretically contain thousands of barcodes each. After identifying the most diver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 49 publications
(54 reference statements)
6
60
0
Order By: Relevance
“…However, we have successfully used RCA to amplify and rescue infectious virus from several infectious cDNA clones. These include emerging zoonotic viruses (Usutu virus; Genus Flavivirus , Family Flaviviridae ) ( Bates et al, 2020 ), and other medically relevant viruses including, Zika virus (Genus Flavivirus , Family Flaviviridae ) ( Weger-Lucarelli et al, 2018 ), West Nile virus (Genus Flavivirus , Family Flaviviridae ) ( Grubaugh et al, 2016 , 2017 ), chikungunya virus (unpublished data; Genus Alphavirus , Family Togaviridae ), and SARS-CoV-2 (unpublished data; Genus Betacoronavirus , Family Coronaviridae ). We anticipate that this system can be used for other positive-sense RNA virus cDNA clones and likely negative-strand viruses as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have successfully used RCA to amplify and rescue infectious virus from several infectious cDNA clones. These include emerging zoonotic viruses (Usutu virus; Genus Flavivirus , Family Flaviviridae ) ( Bates et al, 2020 ), and other medically relevant viruses including, Zika virus (Genus Flavivirus , Family Flaviviridae ) ( Weger-Lucarelli et al, 2018 ), West Nile virus (Genus Flavivirus , Family Flaviviridae ) ( Grubaugh et al, 2016 , 2017 ), chikungunya virus (unpublished data; Genus Alphavirus , Family Togaviridae ), and SARS-CoV-2 (unpublished data; Genus Betacoronavirus , Family Coronaviridae ). We anticipate that this system can be used for other positive-sense RNA virus cDNA clones and likely negative-strand viruses as well.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the enzyme replicates DNA with high fidelity due to its 3′—5’exonuclease—or proofreading—activity ( Garmendia et al, 1992 ). We have previously used RCA to rescue infectious cDNA clones; however, in these studies, the RCA product was linearized with endonucleases, column purified, and then transfected ( Weger-Lucarelli et al, 2018 ; Aliota et al, 2018 ). In this study, using a clone driven by a cytomegalovirus (CMV) promoter, we show that peak virus yields were similar following the direct transfection of RCA- and plasmid-derived cDNA clones in several cell lines and that small amounts of the RCA product could be used to rescue virus successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Several of these studies revealed founder effects, an extreme reduction in viral population diversity in which a small sub-population of viruses invade a new tissue or host. This has been described for viruses of plants (8) and animals, including HIV (9), HCV (10), Zika (11,12), influenza (3,13), and poliovirus (6). The gastrointestinal (GI) tract restricts dissemination of lumenal contents, including enteric viruses.…”
Section: Introductionmentioning
confidence: 94%
“…Bacteria-Free Cloning. Site-directed mutagenesis (SDM) was performed using a bacteria-free cloning method essentially as previously described (27). Mutated fragments of the USUV TMN and UG clones were amplified by PCR using Platinum SuperFi 2X PCR Master Mix with mutagenic primers (Supp.…”
Section: Construction Of Usuv Infectious Clonesmentioning
confidence: 99%